Peningkatan perilaku sosial kesehatan melalui pengetahuan tentang diabetes gestasional pada ibu hamil - Nisa'i Daramita Supriyono; Santy Irene Putri; Novi Budi Ningrum; Dewi Kurnia Sari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Diabetes during pregnancy is a health issue that can increase the risk of complications for both the mother and the fetus. Limited knowledge and suboptimal health behaviors can hinder efforts to prevent diabetes during pregnancy. Therefore, health education is needed to improve pregnant women's understanding and awareness regarding gestational diabetes. Purpose: To improve the knowledge and health-related social behaviors of pregnant women through community-based health education activities focused on preventing diabetes during pregnancy. Method: This community service activity was conducted in the Tlogomas neighborhood of Malang City, targeting pregnant women residing in the area. The activity employed educational and health-promotion approaches aimed at increasing knowledge and reinforcing health-related social behaviors among the participants through health counseling on diabetes during pregnancy. Twenty pregnant women participated, actively engaging throughout the entire program. Participant knowledge and understanding were assessed using a one-group pretest-posttest design. Evaluation involved descriptive analysis, calculating mean scores, percentages, and the improvement in participants' knowledge scores. The results are presented in tables and narrative form to illustrate the effectiveness of the educational activity in enhancing pregnant women's knowledge about diabetes and the importance of health behaviors that support diabetes prevention during pregnancy. Results: The study showed that the mean age of respondents was 33.1 years, with the majority (70.0%) falling within the 30–39 age range. Most respondents (65.0%) had a high school education. There was a proportional improvement in respondents' knowledge levels: the